2016
DOI: 10.12688/f1000research.7235.1
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Urinary Tract Reconstruction for Neuropathic Bladder in Children

Abstract: Neuropathic bladder usually causes several limitations to patients’ quality of life, including urinary incontinence, recurrent urinary tract infections, and upper urinary tract damage. Its management has significantly changed over the last few years. The aim of our paper is to address some salient features of recent literature dealing with reconstructive procedures in pediatric and adolescent patients with lower urinary tract dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 49 publications
(48 reference statements)
1
3
0
Order By: Relevance
“…Regarding the operative period, the length of hospitalization for this surgery, mentioned by other studies, ranged from seven to 9.7 days, 3,15,17 which approached the temporality found in the results of this research.…”
Section:  Thematic Category 2: Surgery Difficulties Represented By Tsupporting
confidence: 80%
See 2 more Smart Citations
“…Regarding the operative period, the length of hospitalization for this surgery, mentioned by other studies, ranged from seven to 9.7 days, 3,15,17 which approached the temporality found in the results of this research.…”
Section:  Thematic Category 2: Surgery Difficulties Represented By Tsupporting
confidence: 80%
“…Additional procedures for the acquisition of social continence are required in some cases, for example the creation of a catheterizable canal (ostomy continent by Mitrofanoff technique) as a means to provide more convenient access when urethral catheterization it's hard or impossible. 3 In this study, it was found that only one child needed the construction of the Mitrofanoff conduit in order to facilitate auto-CIL. Such surgical intervention was positively associated with improved QOL, as it provided the patient with the independence to empty their own bladder.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Surgical options that have been developed to increase bladder outlet resistance in the treatment of neurogenic sphincteric incompetence are bladder neck sling, bladder neck reconstruction, artificial urinary sphincter (AUS), and injection of bulking agents [1,2,4e6]. These bladder outlet procedures can be combined with bladder augmentation to improve bladder capacity and/or continent catheterizable urinary channel for catheterization [1,2,4,5]. Unfortunately, reports on long-term results are scarce.…”
Section: Resultsmentioning
confidence: 99%